Efektivitas Media Pembelajaran Discord Terintegrasi Flipped Classroom dan Guided Inquiry Learning pada Materi Laju Reaksi Terhadap Hasil Belajar Peserta Didik - Akmar, Reza; Mawardi, Mawardi; Ulianas, Alizar; Aini, Faiza Qurrata (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to determine the effectiveness of Discord instructional media integrated with flipped guided inquiry learning on reaction rates on students’ learning outcomes. The instructional media has been tested for its validity and practicality prior to the study. The study was conducted using quasi-experimental with pretest-posttest non-equivalent control group design. Sample consists of 72 students from SMA Negeri 13 Padang participated in this study, with class F1 and F2 as the experiment and control group respectively. Students’ learning outcomes were assessed with instrument consisting of multiple choices questions. Results shown the higher N-gain value from experimental group with 0.70 compared to control group with 0.33. Furthermore, the t-test results yielded a value of t-count = 8.11 > t-table = 1.99, indicating that the means were statistically significant. These findings suggest Discord instructional media integrated with flipped guided inquiry learning was effective to improve students’ learning outcomes.